Reformation of the marginal band of avian erythrocytes in vitro using calf-brain tubulin: peripheral determinants of microtubule form (The Rockefeller University Press, 1984)
The microtubules of nucleated erythrocytes form an extraordinary structure: they are organized into a marginal band at the periphery of the cell. This unusual organelle, recurring in detail in each cell, provides an excellent opportunity to study the determinants of microtubule form. We have been able to reform the marginal band, using detergent-extracted erythrocytes that have been depleted of microtubules in vivo and phosphocellulose-purified tubulin from calf brain. We find that detergent-extracted cytoskeletons incubated under these conditions again have microtubules, and that the pattern of these microtubules recapitulates several features of the intact marginal band. In particular, most of the microtubules after regrowth are located in a band at the periphery of the cell, and curve to form an ellipse. These results support the hypothesis that the specification of microtubule location and shape in these cells is governed by determinants that reside at the periphery of the cell.